1183 Three-dimensional echocardiographic paramenters for mitral valve quantification: a feasibility and validation study. (17th January 2020) - Tafciu, E; Granata, G; Ancona, F; Stella, S; Capogrosso, C; Ingallina, G; Melillo, F; Castiglioni, A; De Bonis, M; Alfieri, O; Agricola, E
Abstract: Introduction: Mitral regurgitation (MR) severity affects prognosis and a correct quantification is key for surgical indication. A multiparametric approach (MPA) is recommended, as singular parameters suffer pitfalls. Recently suggested three-dimensional echocardiographic (3DE) parameters lack clear reference values. No studies have assessed the feasibility of regurgitant volume (RV) and fraction (RF) using the 3D planimetric area of the mitral annulus (MAA) and of the left ventricular outflow tract (LVOTA). Purpose To assess the feasibility and reliability of 3DE, RV and RF obtained by doppler volumetric method using MAA and LVOTA, compare results with 2DE and 3D vena contracta area (VCA) and propose cut-offs for these parameters using MPA as gold standard. Methods Patients referred to our Department for MR assessment were enrolled from September 2018 to February 2019 without more than mild aortic regurgitation or severe stenosis, mitral stenosis and previous valvular surgery. Transthoracic 2DE was used to calculate a multiparametric index of MR severity including: jet area/left atrium (LA) area, CW characteristics, 2D vena contracta, PISA, pulmonary vein flow, LA volume and systolic pulmonary artery pressure. Transoesophageal 3DE was used to assess MAA and LVOTA from a 3D dataset. RV and RF were calculated by Doppler volumetric method using the planimetric areas instead of diameters. VCA 3D was calculated from a 3D color dataset as the cross-sectional area of the regurgitant jet. We compared the results between 2DE and 3DE and between functional and organic MR. ROC curves were analyzed to assess diagnostic performance and identify cut-offs for severity prediction. Intraclass correlation coefficient was calculated to assess variability in measurements. Results Population was composed by 87 patients (56 male, 65 ± 13 years), 72% organic MR. MAA was larger in 2DE (10.4 ± 3.2 vs 9.8 ± 2.9 cm2, ) as was the RV (76.6 ± 36.1 vs 66.4 ± 31.9 ml) and RF (55.4 ± 12.4 vs 50.4 vs 10.9%, all p < 0.0001), while LVOTA was smaller (3.9 ± 0.98 vs 4.1 ± 1.0 cm2, p < 0.0001). RV 2D and RF 2D were larger in the organic MR group (p < 0.0001), meanwhile VCA 3D, RV 3D and RF 3D did not show a significant difference (all p > 0.1). VCA 3D had a good correlation with RV 3D (r = 0.593, p < 0.0001) and RF 3D (r = 0.576, p < 0.0001). We proposed a cut-off value of 41.5 mm2 for VCA 3D (94% sens, 96% spec, AUC 0.978), 52 ml for RV 3D (84% sens, 78% spec, AUC 0.901) and 47.6% for RF 3D (91% sens, 90% spec, AUC 0.966) to predict MR severity as assessed by MPA. Intraclass correlation coefficient was 0.980 for MAA and 0.985 for LVOTA for intra-observer variability, while for inter-observer variability it was 0.951 for MAA and 0.962 for LVOTA. Conclusion: 2DE overestimates MA dimensions and underestimates LVOT dimensions thus overestimating RV and RF. 3DE measures are relatively simple and reproducible. Proposed cut-offs for RV, RF and VCA 3D have a good diagnostic power.